Intravenous treprostinil infusion via a fully implantable pump for pulmonary arterial hypertension - Ewert, Ralf; Grünig, Ekkehard (Clinical research in cardiology, 2017)
ObjectivesParenteral prostanoids infused via external pumps are well-established pulmonary arterial hypertension (PAH) treatments. However, local side-effects and systemic infections restrict their use. The purpose of this study was to investigate the safety of a fully implantable treprostinil infusion pump (LENUS Pro®) in patients with PAH.MethodsThirty patients with PAH undergoing pump implantation (with stable PAH therapy for ≥3 weeks pre-implantation) were included in this prospective, multicenter, observational study (NCT01979822). Primary endpoints were predefined adverse events (AEs) during implantation, in-hospital and/or during 6-month follow-up. Refill-related AEs were a secondary endpoint.ResultsTwenty-nine patients completed 6-month follow-up (one underwent lung transplantation). During implantation, one pneumothorax (not requiring drainage) occurred. Four patients had an in-hospital AE (including one catheter revision). During 6-month follow-up, AEs were most frequent at the first refill (10); the most common AE was seroma around the pump. No infections occurred. One pump required replacement because of a defective septum caused by use of a non-approved refill needle (associated with extravasation). Apart from the extravasation, no refill-related AEs were recorded. Post hoc efficacy analyses showed significant improvements in functional class [number in functional class I/II/III/IV: 0/5/21/2 (baseline) versus 3/8/17/0 (6 months); p = 0.012] and 6-min walk distance (mean ± standard deviation: 407 ± 122 m versus 445 ± 127 m; n = 17; p = 0.014).ConclusionsThis study supports use of a fully implantable treprostinil infusion pump in patients with PAH requiring parenteral prostanoids. Refills should be performed by specialized healthcare professionals at patients’ homes or at experienced centers using approved equipment.
Gesehen am 09.11.2018